OFFSHORE JACKET PLATFORMS – LRFD CODE CALIBRATION - Sambu Potty, Narayanan (2010)
A large number of the approximately 200 platforms in Malaysia have exceeded their design lives. New platforms are being designed and installed. Any reduction in the assessment of design loads or resistances of the structures can translate into substantial savings in the design of the platform. Further, this can lead to reductions in consumption of precious resources like steel and reduce the carbon footprint. LRFD provide a simple, safe and economically efficient way of designing offshore platforms to different load conditions and is able to incorporate regional practices in design. LRFD considers the variability in parameters through the use of safety factors. Safety factors are determined by calibration and can be component based or system based. API RP2A LRFD and ISO are such codes. Codes provide standardization and optimal use of resources using calibration. LRFD is apt for re-evaluation of old platforms for changes in loads and changes in resistances due to deterioration. The aim is to produce structures that have uniform and acceptable reliability. This work examines how the load factors have been calibrated in the different regions and the results are presented. The lessons learned from these calibration efforts are presented. Conclusions are drawn from these studies.